National Integrated School Health Screening Program in Iran - A Amirkhani; SM Alavian; M Dashti; T Aminaie; G Ardalan; H Ziaoddini; R Kelishadi (Tehran University of Medical Sciences, 2009)
Background: Screening program in schools are designed to identify children who have early signs of health problems. This study provides information about the findings of national screening program in Iran. Methods: This national program is conducted by the Ministry of Health& Medical Education (MOHME) with collaboration of the Ministry of Education & Training. This program had two major parts including 1) screening of behavioral, hearing and visual disorders, pediculosis and calculating body mass index and 2) physical examination of students, conducted by primary care physicians. All services are offered free of charge. The students' parents are informed about the health status of their children. Results: The screening program conducted in 2007-2008 included 3,124,021 students from 33 cities who were studying in the first- and third- grade- students in elementary schools, first- grade- students in middle and high schools. Of total students studied, 12.48% had weight disorders, i.e. body mass index <3rd percentile or > 95th percentile. 4.77% had visual disorders, 3.95 % had head lice, 2.24% had behavioral disorders, and 0.6% had hearing disorders. Conclusion: In addition to its benefits to the students' health status, the results of this screening program help health policy makers to design interventions for prevention and or early detection and treatment of the most common disorders documented among school students.